UJI PALATABILITAS UMPAN TERHADAP JENIS KECOA YANG DITEMUKAN PADA WARUNG MAKAN TEGAL DI KELURAHAN TEMBALANG - Widya Widya; Martini Martini; Praba Ginandjar (Jurnal Kesehatan Masyarakat (Undip), 2018)
Business owners should be free of cockroach density as big as <2. The first step that should be known in developing this control method is knowing the most type of bait that cockroach preferred. This research was conducted with 2 stages, that are palatability test of bait and measuring the density of the cockroach. Bait palatability test is a quasi experiment with the design of post test only control group design approach. And measuring the density of the cockroach is an observational research with cross sectional approach. Types of bait used are milk powder, blueberry jam and peanut butter. The object of this research is the number of cockroaches trapped in each bait that installed in 4 and 25 for cockroach density stalls Tegal food in Tembalang Village. The results of this research indicate that the bait with the highest trap found in the type of peanut butter, where as many as 32 of cockroaches trapped, 12 of cockroaches in milk powder bait and 14 cockroaches in blueberry jam. Based on statistical test results, there is a difference in the number of cockroaches trapped in the types of bait. The bait type of peanut butter more approached by cockroaches than any other types of bait. For cockroach density, there are 20 (80%) of 25 food stalls which have high cockroach density that is > 2 cockroaches, 5 (20%) food stalls which have low cockroach density and 4 food stalls there are no cockroach.